Near-infrared light-heatable platinum nanozyme for synergistic bacterial inhibition - Li, Xue; Zhu, Weisheng; Zhou, Yuan; Wang, Nan; Gao, Xiangfan; Sun, Suling; Cao, Mengting; Zhang, Zhijun; Hu, Guixian (Frontiers in Bioengineering and Biotechnology, 2024)
The development of non-antibiotic strategies for bacterial disinfection is of great clinical importance. Among recent developed different antimicrobial strategies, nanomaterial-mediated approaches especially the photothermal way and reactive oxygen species (ROS) generating method show many obvious advantages. Although promising, the clinical application of nanomaterials is still limited owning to the potential biosafety issues. Further improvement of the antimicrobial activity to reduce the usage, and thus reduce the potential risk, is an important way to increase the clinical applicability of antibacterial nanomaterials. In this paper, an antimicrobial nanostructure with both excellent photothermal effect and peroxidase-like activity was constructed to achieve efficient synergistic antimicrobial activity. The obtained nano-antimicrobial agent (ZIF-8@PDA@Pt) can not only efficiently catalyze the production of ROS from H2O2 to cause damage to bacteria, but also convert photon energy of the near infrared light into thermal energy to kill bacteria, and the two synergistic effects induce in a highly efficient antimicrobial activity. This study not only offers a new nanomaterial with efficient antibacterial activity, but also provides a new idea for constructing synergistic antibacterial properties.